AB0704 Impact of Lumbar Syndesmophyte on Bone Heath as Assessed by Bone Density (BMD) and Bone Texture (TBS) in Men with Axial Spondyloarthritis. (10th June 2014) - Wildberger, L.; Boiadjieva, V.; Hans, D.; Stoilov, N.; Ivanova, M.; Stoilov, R.; Rashkov, R.; Aubry-Rozier, B.
Abstract : Background: Patients with spondyloarthritis (AS) have an elevated incidence of osteoporosis and are at increased risk of pathological vertebral fracture. Evaluation of bone by dual energy X-Ray absorptiometry (DXA) has its limits in fracture prediction, already known in this population, probably because it only measures quantity, but not quality of bone. One hypothesis is that the presence of lumbar syndesmophyte could overestimate the spine BMD. Trabecular bone score (TBS) is a new texture measurement correlated with bone microarchitecture. Previous studies have shown that TBS is not impacted by osteoarthritis and thus could be a predictor of fracture better than spine BMD. Objectives: We aimed to evaluate a male population of AS with BMD and TBS measurement and see the impact of lumbar syndesmophyte Methods: Two cohorts of AS male patients (Lausanne, Sofia) with AS disease, clinical and bone parameters (femoral neck and total spine BMD + spine TBS) were merged. We compared BMD and TBS results regarding to the presence/absence of syndesmophyte and compared to young normative values (T-score for both BMD and TBS). T-tests were used to compare the two groups. Results: Our study concerned 22 men (10 men with lumbar syndesmophytes (L1 to L4, ≥1), 11 without), all fulfilled the ASAS criteria, no difference in age (47 years old) and BMI. Mean spine BMD T-score were 0.098±2.11 and -1.17±0.73 (p<0.05) respectively for AS men with and without syndesmophytes, 0±2.39 and -1.6±0.9 (p<0.05) if vertebrae with osteoarthritis were excluded. Mean femoral neck BMD T-score was -1.95±0.83 and -0.82±071 (p<0.05) respectively for AS men with and without syndesmophytes. Mean TBS was 1.269±0.081 and 1.338±0.083 (p<0.05) and corresponding T-score TBS were -1.395±0.885 and -0.640±0.907 (p<0.05) respectively for AS men with and without syndesmophytes. Conclusions: The two populations (Lausanne and Sofia) had comparable BMD and TBS results, after exclusion of degenerative vertebrae and adjustment for the two DXA machines. As expected, the only "normal" result was spine BMD in AS men with syndesmophytes. Others results were lower than in a normal population. Interestingly, even if men with syndesmophyte had normal spine BMD results, they had lower TBS results than men without syndesmophyte and lower femoral neck BMD. All results are statistically significant. These results have to be confirmed in term of disease activity and fracture risk. In conclusion, spine BMD is erroneously influenced by syndesmophyte unlike spine TBS and femoral BMD. We can recommend to evaluate bone health in AS male population with syndesmophyte by measurement of spine TBS and femoral BMD. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4219